2013
DOI: 10.1007/978-3-642-38946-7_13
|View full text |Cite
|
Sign up to set email alerts
|

Small Induction Recursion

Abstract: Abstract. There are several di↵erent approaches to the theory of data types. At the simplest level, polynomials and containers give a theory of data types as free standing entities. At a second level of complexity, dependent polynomials and indexed containers handle more sophisticated data types in which the data have an associated indices which can be used to store important computational information. The crucial and salient feature of dependent polynomials and indexed containers is that the index types are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Indexed inductive types (which are used in Nordvall Forsberg's construction) are constructed from plain inductive types in Altenkirch et al [3], with good computational properties (provided an identity type that satisfies J strictly). And small induction-recursion is reduced to plain indexed inductive types in Hancock et al [11].…”
Section: Related Workmentioning
confidence: 99%
“…Indexed inductive types (which are used in Nordvall Forsberg's construction) are constructed from plain inductive types in Altenkirch et al [3], with good computational properties (provided an identity type that satisfies J strictly). And small induction-recursion is reduced to plain indexed inductive types in Hancock et al [11].…”
Section: Related Workmentioning
confidence: 99%
“…The reduction of indexed inductive-definitions to Petersson-Synek Trees has been developed in container theory, see esp. [19,14] but as well [6,21]. There are various set theoretic models of final coalgebras, examples are de Bruin [8], Barr [7] or Aczel [4].…”
Section: Related Workmentioning
confidence: 99%
“…They are initial algebras of indexed containers in the theory of containers, see [6,21]. In [14,19] a formal proof that initial algebras of indexed containers and therefore Petersson-Synek trees subsume all indexed inductive definitions is given. We write in the following Tree instead of D and tree for the constructor C. Let us fix in the following A, B, j: Assumption 3.1 (a) In the following assume…”
Section: Initial Algebras and Inductively Defined Setsmentioning
confidence: 99%
“…Since the publication of the LICS paper, indexed containers have been used as a base for the generic definition of datatypes for Epigram 2 (Chapman et al 2010), and to develop the theory of ornaments (McBride 2010). In recent work, it has been shown that indexed containers are sufficient to express all small inductive-recursive definitions (Hancock et al 2013)…”
Section: Related Workmentioning
confidence: 99%